Examining the mediating role of motivation in the relationships between teacher-created motivational climates and quality of engagement in secondary school physical education - Daniel Milton; Paul R. Appleton; Eleanor Quested; Anna Bryant; Joan L. Duda (PLoS ONE, 2025)
Grounded in Duda’s integrated model of the motivational climate, the current study examined the hypothesized mediating role of motivation quality in the relationships between empowering and disempowering teacher-created motivational climates and indicators of quality engagement in secondary school physical education (PE). The hypothesised model was tested cross-sectionally and longitudinally in two separate samples of students. Data were collected via questionnaires measuring the motivational climate, autonomous and controlled motivation and indicators of engagement (enjoyment, concentration and boredom). Cross sectional data collected from 832 students (439 males and 386 females) while longitudinal data stemmed 299 students (166 males and 163 females). All students were from schools in Wales aged between 12 and 15 years. Structural equation modelling was used to test the hypothesised model and the mediating role of autonomous and controlled motivation. The hypothesised model was supported cross-sectionally and longitudinally, indicating that empowering climates positively predicted students’ autonomous motivation for PE, whereas disempowering motivational climates positively predicted controlled motivation. In turn, autonomous and controlled motivation positively and negatively predicted indictors of students’ engagement in PE in the hypothesised directions. Analyses revealed relationships between empowering and disempowering climates with enjoyment, concentration and boredom were indirect via autonomous and controlled motivation. In summary, results support the role of autonomous and controlled motivation in the differential relationships between empowering and disempowering motivational climates and indicators of the quality of student engagement. The findings suggest that targeted professional learning opportunities for PE teachers are needed which facilitate more empowering climates and reducing disempowering strategies.